2021
DOI: 10.1002/ar.24762
|View full text |Cite
|
Sign up to set email alerts
|

Venous networks in the upper airways of bats: A histological and diceCT study

Abstract: Our knowledge of nasal cavity anatomy has grown considerably with the advent of micro‐computed tomography (CT). More recently, a technique called diffusible iodine‐based contrast‐enhanced CT (diceCT) has rendered it possible to study nasal soft tissues. Using diceCT and histology, we aim to (a) explore the utility of these techniques for inferring the presence of venous sinuses that typify respiratory mucosa and (b) inquire whether distribution of vascular mucosa may relate to specialization for derived functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Within the chiropteran sample, they compared nonecholocating bats with oral and nasal emitters of echolocation sounds. Although the study did not link the vascular mucosa to specializations of echolocation behaviors, Smith et al (2022, this volume) were able to quantify mucosal patterns between species in specific areas of interest such as the nasopharyngeal wall versus nasal cavity regions between hipposiderids and phyllostomids. It was found that, despite both hipposiderids and phyllostomids being nasal emitters of echolocation, the former have more numerous and widespread venous sinuses whereas the latter had mucosa that is not as well vascularized.…”
Section: From Gills To Suckling a Composite Evolutionary History Of T...mentioning
confidence: 99%
See 2 more Smart Citations
“…Within the chiropteran sample, they compared nonecholocating bats with oral and nasal emitters of echolocation sounds. Although the study did not link the vascular mucosa to specializations of echolocation behaviors, Smith et al (2022, this volume) were able to quantify mucosal patterns between species in specific areas of interest such as the nasopharyngeal wall versus nasal cavity regions between hipposiderids and phyllostomids. It was found that, despite both hipposiderids and phyllostomids being nasal emitters of echolocation, the former have more numerous and widespread venous sinuses whereas the latter had mucosa that is not as well vascularized.…”
Section: From Gills To Suckling a Composite Evolutionary History Of T...mentioning
confidence: 99%
“…One of the many adaptations of bats includes the ability to hunt and navigate using echolocation. While some have studied skeletal adaptations for echolocation in the nasal cavities and upper airways of bats (Curtis et al, 2020; Curtis & Simmons, 2017), Smith et al (2022, this volume) focus on soft tissues of the noses and nasopharynges of several bat species, specifically epithelial distribution and the presence of subepithelial venous sinuses. They use diffusible Iodine‐based Contrast‐enhanced CT (diceCT) in conjunction with traditional histology to provide a fascinating analysis of two different methods for analyzing the presence of submucosal blood sinuses in the nasal cavities of bats.…”
Section: From Gills To Suckling a Composite Evolutionary History Of T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mammals have plate-like structures called turbinals in the nasal cavity which possess bony or cartilaginous plate-like structures inside them (Moore 1981;Smith et al 2015;Smith et al 2021a). The turbinal expands the surface area in the nasal cavity by complex branching and scrolling (Parker 1874;Parker 1885;Martineau-Doizé et al 1992;Smith et al 2021aSmith et al , 2021b. Depending on their localization, the tissue on the surface of the turbinal is characterized by a large number of secretory goblet cells and capillaries and olfactory receptors (Negus 1958;Smith et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…The turbinal expands the surface area in the nasal cavity by complex branching and scrolling (Parker 1874;Parker 1885;Martineau-Doizé et al 1992;Smith et al 2021aSmith et al , 2021b. Depending on their localization, the tissue on the surface of the turbinal is characterized by a large number of secretory goblet cells and capillaries and olfactory receptors (Negus 1958;Smith et al 2021b). Therefore, the turbinals have functions, such as warming the air from the outside world and absorbing water from the exhaled breath, and a role in olfaction (Negus 1958;Hillenius 1992).…”
Section: Introductionmentioning
confidence: 99%